2021
DOI: 10.1111/jcmm.16874
|View full text |Cite
|
Sign up to set email alerts
|

Imipramine impedes glioma progression by inhibiting YAP as a Hippo pathway independent manner and synergizes with temozolomide

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…Moreover, the silencing of YAP1 caused further impairment in autophagic flux, as well as an exacerbation in caspase 3 activation and cell death upon dipyridamole treatment. A recent study has reported that imipramine impedes glioma progression with concurrent cAMP elevation and YAP1 inhibition [ 44 ]. We found that glioma cells with YAP1 depletion showed decreased viability without signs of caspase 3 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the silencing of YAP1 caused further impairment in autophagic flux, as well as an exacerbation in caspase 3 activation and cell death upon dipyridamole treatment. A recent study has reported that imipramine impedes glioma progression with concurrent cAMP elevation and YAP1 inhibition [ 44 ]. We found that glioma cells with YAP1 depletion showed decreased viability without signs of caspase 3 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Normal human astrocyte (NHA) was purchased from ScienCell. GBM1 and GBM2 are primary glioma cells established by our laboratory [ 36 , 37 , 38 ]. Normal human astrocyte was cultured in astrocyte medium (ScienCell; Cat No.1801), while glioma cells were cultured in Dulbecco’s modified Eagle medium (DMEM) and supplemented with 10% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…U251 and GBM1 cell lines over-expressing YAP were constructed by lentiviral transfection as described previously [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover a multivariate analysis showed that high expression of fascin protein was an independent predictor of the prognosis of patients with glioma [110]. Intriguingly, Wang et al showed that the TCA with anti-fascin activity, imipramine, significantly retarded the proliferation of primary and immortalized glioma cells by inhibiting YAP protein, a recognized oncogene in glioma [56].…”
Section: Cancer Of Central Nervous Systemmentioning
confidence: 99%